From Risk to Trust: Strengthening QRIS Usage in MSMEs for Islamic Financial Inclusion - Rony Arpinto Ady; Lintang Pamugar Mukti Aji; Endah Kristiani (ITB AAS INDONESIA Surakarta, 2026)
Wider access to QRIS has strengthened the digital payments environment for Indonesian micro, small, and medium-sized enterprises, yet regular use is still shaped by how users evaluate financial information and security-related uncertainty. Based on responses from 180 MSME customers in Yogyakarta who had completed at least one QRIS payment, this research examined the interplay of financial literacy, perceived security risk, trust in QRIS security, behavioural intention and actual usage using Partial Least Squares Structural Equation Modelling, and the analysis. The analysis confirms that financial literacy encourages adoption in two main ways: it increases willingness to use QRIS and fosters stronger trust in the system’s security. At the same time, perceptions of security risk work in the opposite direction. When users remain concerned about fraud, data exposure, or similar threats, both trust and behavioural intention decline. Trust then becomes a pivotal mechanism in the adoption process, as it contributes positively to intention as well as actual QRIS use. The analytical model also accounts for a substantial share of the variation in realised usage behaviour. A further result concerns the interaction effect: trust significantly moderates the link between behavioural intention and actual usage, but the direction is negative. This suggests that once users already trust QRIS and have incorporated it into their payment habits, stronger intention adds only limited incremental influence to their level of actual use. The overall implication is that broader QRIS adoption among MSMEs depends on simultaneous progress in financial literacy, risk reduction, and visible security assurance. Viewed from the perspective of Islamic finance, the results also indicate thatt Islamic banks, Islamic microfinance institutions, and other sharia-compliant intermediaries are well positioned to encourage digital financial inclusion by linking QRIS expansion with financial education and reliable payment security.